MORADABAD GHARANA: ORIGIN, EVOLUTION AND CULTURAL LEGACY IN HINDUSTANI CLASSICAL MUSIC - Kaur, Mandeep; Parmar, Sharanjit Kaur (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Moradabad Gharana represents an important but less studied tradition in the broad spectrum of Hindustani classical music. This paper examines the historical origins, developmental process and cultural contributions of the Moradabad musical tradition, following its evolution from the early 17th century to contemporary manifestations. Through a comprehensive analysis of historical sources, genealogical records and musical characteristics, this study shows how the Moradabad Gharana emerged as a distinctive musical lineage, and eventually contributed to the establishment of the famous Bhendi Bazaar Gharana in Mumbai. The research methodology includes archival research, analysis of musical recordings, and examination of the socio-political factors that influenced the migration patterns of the gharana. The main findings indicate that the Moradabad tradition, while rooted in the cultural milieu of Mughal-era North India, continued to display remarkable adaptability and innovation, particularly in sarangi playing and khyal singing. The research paper concludes that despite geographical displacement and changing patronage systems, the musical legacy of the Moradabad gharana continues to influence contemporary Hindustani classical music, particularly through its emphasis on vocal ornamentation and rhythmic sophistication.